Design and strength analysis of a test bench for brake calipers on suspended monorail trains - JIANG Yongzhi; XIE Afu; LIU Wenjie; RAN Shuai; WU Pingbo (机车电传动)
Brake calipers serve as the actuators in braking systems and are critical components for ensuring the safe operation of trains. However, there is currently a lack of dedicated test benches for brake calipers used on suspended monorail trains that employ a track beam braking system. To verify the safety and reliability of these brake calipers, this paper presents the design of a test bench for testing and evaluating braking system performance. The bench comprises several independent modules, including a condition simulation mechanism and a brake caliper adjustment mechanism. Based on the structural design, 3D models were established for both the test bench and the brake calipers. Subsequently, simulation analyses were performed using finite element analysis software to calculate the deformation and equivalent stress of various components subjected to loading under working conditions, specifically focusing on the brake calipers and the sprocket drive shaft within the condition simulation mechanism. The simulation results indicate that both the deformation and maximum equivalent stress of the brake calipers fall within the yield strength and elastic deformation limits of Q345 steel. Similarly, the total deformation and maximum equivalent stress of the drive shaft are within the yield strength and elastic deformation limits of 45 steel. These findings align with the design requirements and provide guidance and a basis for subsequent structural optimization.